Governor's Palace, Trinidad, B.W.I. - (:unkn) unknown (Waterman, Trinidad, 2009)
The Governor's residence, until 1976 when Trinidad and Tobago became a republic and the house was subsequently designated "The President's House", surrounded by the tropical flora of the Botanical Gardens.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Public buildings--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Botanical gardens--Trinidad and Tobago; Architecture--Trinidad and Tobago; President's House, The